“New Colonisers” Play in Postcolonial Music Education in Mauritius - Marie-Christinne B. Clarisse (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2020)
Indo-Mauritian group cultural hegemony has become a trend in music education in Mauritius. This fact has led to social imbalances and inequality of art education. In this situation, Mauritius needs openness and a new policy of arts education, and this must be taken into account because Mauritius has a diverse population. The problem is how the condition of postcolonial music education affects the art education policy in Mauritius. This study aims to uncover this problem. The approach taken is based on an ethnographic approach using a grounded theory strategy. In a postcolonial context and highly multicultural society, hegemonic forces are at play that promotes the Hindu majority ethnic group (termed the “new colonizers”) over all the other ethnic groups. This argument is supported on one side by an analysis of the public music education system, and on the other, by the process of teacher training and certification. An analytic autoethnographic method grounded in a transformative philosophical perspective informs this qualitative research. Results demonstrate a substantial disparity of opportunities for students and prospective music teachers in favor of the Hindu ethnic group. An intercultural perspective on music education in Mauritius is provided that could portray Mauritian nationhood within the public music education system.